2020
DOI: 10.1021/acsami.9b22622
|View full text |Cite
|
Sign up to set email alerts
|

Unassisted Water Splitting Using Standard Silicon Solar Cells Stabilized with Copper and Bifunctional NiFe Electrocatalysts

Abstract: Silicon photovoltaic cells functionalized with water-splitting electrocatalysts are promising candidates for unassisted water splitting. In these devices, the total surface of silicon solar cells is covered with electrocatalysts, causing issues with (i) stabilizing silicon solar cells in water and (ii) device efficiency due to parasitic optical absorption in electrocatalysts. We describe and validate a water-splitting device concept using a crystalline silicon solar cell where the front side is covered with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Additionally, a crucial merit of this photoelectrode is that it is easier to control the photovoltage and photocurrent using a tandem or module structure, which provides a substantial advantage in constructing a suitable photoelectrode for the generation of specific target products. [ 32 ] Comparing LDH/Ni/eu@nfOP and a two‐series‐module‐type structural photoanode (denoted as 2m‐LDH/Ni/eu@nfOP, Figure S23, Supporting Information), the onset potential of 2m‐LDH/Ni/eu@nfOP is ‐0.28 V versus RHE, as shown in Figure 3d; this corresponds to a negative shift of 0.83 V compared to the onset potential of LDH/Ni/eu@nfOP. Further, the current density of 2m‐LDH/Ni/eu@nfOP is 7.59 mA cm –2 at 1.23 V versus RHE, which is approximately twice less than that of LDH/Ni/eu@nfOP.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a crucial merit of this photoelectrode is that it is easier to control the photovoltage and photocurrent using a tandem or module structure, which provides a substantial advantage in constructing a suitable photoelectrode for the generation of specific target products. [ 32 ] Comparing LDH/Ni/eu@nfOP and a two‐series‐module‐type structural photoanode (denoted as 2m‐LDH/Ni/eu@nfOP, Figure S23, Supporting Information), the onset potential of 2m‐LDH/Ni/eu@nfOP is ‐0.28 V versus RHE, as shown in Figure 3d; this corresponds to a negative shift of 0.83 V compared to the onset potential of LDH/Ni/eu@nfOP. Further, the current density of 2m‐LDH/Ni/eu@nfOP is 7.59 mA cm –2 at 1.23 V versus RHE, which is approximately twice less than that of LDH/Ni/eu@nfOP.…”
Section: Resultsmentioning
confidence: 99%
“…Dabirian et al reported an Si photocathode functionalized with Cu/NiFe-LDH electrocatalysts. 117 Due to the high catalytic activity of NiFe-LDH, the photocathode achieved STH efficiency of 11.31% under no-bias condition and stability of about 33 h in 1.0 M NaOH electrolyte.…”
Section: Modification Of Oer Cocatalystsmentioning
confidence: 99%
“… 137 The as‐prepared n‐Si/a‐TiO 2 /NiFe LDH photoanode without the buried junction showed a high photocurrent density of 36 mA cm −2 at 1.23 V vs. RHE, and operated more stably compared to n‐Si/NiFe LDH. Dabirian et al reported an Si photocathode functionalized with Cu/NiFe‐LDH electrocatalysts 117 . Due to the high catalytic activity of NiFe‐LDH, the photocathode achieved STH efficiency of 11.31% under no‐bias condition and stability of about 33 h in 1.0 M NaOH electrolyte.…”
Section: Strategies For Enhancing Pec Performancementioning
confidence: 99%
“…For example, the traditional Si solar cells, which have been commercially used, still need to encapsulate the active layers with glass and poly(methyl methacrylate) (PMMA) to avoid contact with water. [ 8 ] The most popular absorber at present is CH 3 NH 3 PbI 3 , which would directly react with water molecules. [ 9 ] The as‐formed perovskite films would decompose under the ambient atmosphere, and the device fabrication processes must be conducted in the inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…To protect the functional layers and maintain the normal operation of solar cells, the encapsulation layer has to be meticulously designed according to varied real situations, which greatly impedes large-scale industrialization applications. [3][4][5][6][7][8] Therefore, developing encapsulation-free solar cells with great water tolerance is highly desirable. However, the progress in this field is quite frustrated due to two obstacles.…”
Section: Introductionmentioning
confidence: 99%